Mass flow and particle size monitoring of pulverised fuel vertical spindle mills - Archary Hamresin; Schmitz Walter; Jestin Louis (Chemical and Process Engineering)
The first step towards condition based maintenance of the milling plant is the implementation of online condition monitoring of the mill. The following paper presents and analyses methods of monitoring the key performance factors of a vertical spindle mill that is suited for implementation on older power stations, i.e. the quantity (mass flow rate) and quality (particle fineness) of the pulverised fuel produced by the mill. It is shown herein that the mill throughput can be monitored on-line using a simple mill energy balance that successfully predicts the coal throughput within 2.33% as compared to a calibrated coal feeder. A sensitivity analysis reveals that the coal moisture is a critical measurement for this method to be adopted as an on-line mass flow monitoring tool. A laser based particle size analyser tool was tested for use in the power plant environment as an online monitoring solution to measure pulverised fuel fineness. It was revealed that several factors around the set-up and operation of the instrument have an influence on the perceived results. Although the instrument showed good precision and repeatability of results, these factors must be taken into account in order to improve the accuracy of the reported results before the instrument can be commissioned as an on-line monitoring solution.